2019
DOI: 10.1007/s12630-019-01493-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cirrhosis in patients undergoing cardiac surgery: a retrospective observational cohort study

Abstract: Purpose Patients with cirrhosis and concomitant coronary/valvular heart disease present a clinical dilemma. The therapeutic outcome of major cardiac surgery is significantly poorer in patients with cirrhosis compared with patients without cirrhosis. To address this, we aimed to identify associations between the severity of cirrhosis and post-cardiac surgical outcomes. Methods A historical cohort analysis of patients undergoing cardiac surgery at the University of Alberta Hospital from January 2004 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 34 publications
6
13
0
Order By: Relevance
“…Then, there were 13 studies left for qualitative synthesis. Finally, seven eligible studies were included in this analysis [ 13 14 15 16 17 18 19 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, there were 13 studies left for qualitative synthesis. Finally, seven eligible studies were included in this analysis [ 13 14 15 16 17 18 19 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this pooling-up analysis was to figure out if there was an impact of LC on cardiac surgery. A total of seven studies containing 1,535,129 patients who underwent cardiac surgery were included [ 13 14 15 16 17 18 19 ]. All seven studies reported LC and non-LC groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eventually, despite especially MELD score gives indisputably useful precepts to quantify the severity of chronic hepatopathy, it seems necessary to develop a more specific new risk score dedicated to cirrhotic patients having to undergo cardiac surgery in the respect of the impact of liver disease on final clinical outcome [7].…”
Section: Discussionmentioning
confidence: 99%